Shelter from the storm [large type] - Davids, Patricia (North Country Amish, 2021)
"Enjoy this wonderful Amish romance from USA Today bestselling author Patricia Davids A marriage of convenience might just be the answer to her prayers... Secretly pregnant and unwed, Gemma Lapp has a difficult choice--face her Amish community or raise her baby alone. But when a storm strands Gemma in the wilderness with her former crush, Jesse Crump, she knows her secret won't be safe for long. Gemma can't imagine trusting a man again...until Jesse proposes a marriage of convenience. Could their arrangement lead to love? From Love Inspired: Uplifting stories of faith, forgiveness, and hope. This book is part of the list: Thorndike Press Large Print Amish Fiction"--